Inducible SMARCAL1 knockdown in iPSC reveals a link between replication stress and altered expression of master differentiation genes - Giusj Monia Pugliese; Federico Salaris; Valentina Palermo; Veronica Marabitti; Nicolò Morina; Alessandro Rosa; Annapaola Franchitto; Pietro Pichierri (The Company of Biologists, 2019)
Schimke immuno-osseous dysplasia is an autosomal recessive genetic osteochondrodysplasia characterized by dysmorphism, spondyloepiphyseal dysplasia, nephrotic syndrome and frequently T cell immunodeficiency. Several hypotheses have been proposed to explain the pathophysiology of the disease; however, the mechanism by which SMARCAL1 mutations cause the syndrome is elusive. Here, we generated a conditional SMARCAL1 knockdown model in induced pluripotent stem cells (iPSCs) to mimic conditions associated with the severe form the disease. Using multiple cellular endpoints, we characterized this model for the presence of phenotypes linked to the replication caretaker role of SMARCAL1. Our data show that conditional knockdown of SMARCAL1 in human iPSCs induces replication-dependent and chronic accumulation of DNA damage triggering the DNA damage response. Furthermore, they indicate that accumulation of DNA damage and activation of the DNA damage response correlates with increased levels of R-loops and replication-transcription interference. Finally, we provide evidence that SMARCAL1-deficient iPSCs maintain active DNA damage response beyond differentiation, possibly contributing to the observed altered expression of a subset of germ layer-specific master genes. Confirming the relevance of SMARCAL1 loss for the observed phenotypes, they are prevented or rescued after re-expression of wild-type SMARCAL1 in our iPSC model. In conclusion, our conditional SMARCAL1 knockdown model in iPSCs may represent a powerful model when studying pathogenetic mechanisms of severe Schimke immuno-osseous dysplasia.